Ceratofacia com novo biomaterial: etapas de desenvolvimento visando à remodelação corneana usando implante intracorneano - Silva, Maria Carolina Marquezan Da [UNIFESP] (2020)
Purpose: To describe a new approach for corneal remodeling. Methods: Some pilot studies were conducted to practice handling and implanting the lenticule for corneal remodeling technique. At the final study, it was used a new biocompatible agent, collagen type 1, excimer laser shaped, measured approximately 240 micrometers (μm) and inserted intrastromal post mortem pig eyes. The biomaterial was shaped with the excimer laser on the posterior surface to create planoconcave shapes, which were divided in three different groups and inserted into a manually dissected stromal pocket, at approximately 200 micrometer (μm) depth. Group A (three eyes) 70 μm maximal ablation depth; group B (three eyes) 64 μm maximal ablation depth, and group C (three eyes) 104 μm maximal ablation depth, with a lost of total central thickness (central hole, created unscheduled). Group D (three eyes) was included as a control group with creation of a pocket but without insertion of biomaterial. Evaluation of porcine eyes was performed by optical coherence tomography (AS-OCT Visante®) and corneal tomography (Pentacam®). Results: Pentacam® showed that the average keratometry (Km) in group A decreased from 36.80 to 28.90. Reduction was observed in group B, in which Km decreased from 34.00 to 33.88, and in group C, Km decreased from 34.67 to 32.13. For control group D, Km decreased from 33.78 to 33.12. Corneal flattening was more evident in the biomaterial (A, B and C) implant groups, with a larger reduction in Km (delta 3.52) compared to the control group (delta 0.67), but this reduction was not statistically significant (p=0.405). When K1 and K2 were evaluated separately, between the groups with the intrastromal implant, there was a statistically significant reduction (p=0.021) of K1. The OCT corneas of groups A, B and C showed the implant located in the anterior stroma and with displacement of the endotelial face backward, which was not observed in the control group. The main complications occurred performing the pocket, sometimes very deep, or superficial, as well as the tearing of the implant during the intrastromal insertion, especially during the first experiments in the pilot study, as well as the liquid leakage during the sample excimer laser treatment. Conclusions: The novel planoconcave biomaterial implant was able to reshape the cornea in a post mortem model, resulting in flattening of the cornea. This approach could represent a novel treatment for refractive error in eyes not amenable to currently available technique options such as those with high myopia and corneal ectasia, as well as other refractive errors, according to the lenticule shape, as aphakia and hyperopia.